Prevalence and types of medication errors in pro re nata medication orders among hospitalized patients: a cross-sectional study - Arefeh Rasouli-Rad; Mahdi Ahmadinia; Azadeh Eshraghi; Hamidreza Aslani; Zahra Karimian; Akram Hashemi; Maryam Farasatinasab (Journal of Pharmaceutical Health Care and Sciences)
Abstract Background Medication errors in Pro Re Nata (PRN) prescriptions pose a significant threat in hospital settings, especially due to unclear prescribing practices. Despite growing attention to patient safety, documentation for PRN orders remains poor, increasing the risk of medication errors and adverse drug events. To assess the prevalence and types of PRN medication errors in hospitalized patients, identify high-risk drugs, and explore factors linked to prescribing errors. Methods This cross-sectional study was conducted in 2023 at an Educational and Research Hospital. It included 400 hospitalized patients who had received at least one PRN prescription. Data were collected using a standardized extraction form based on clinical guidelines and expert consultation. Chi-square tests and logistic regression were used to evaluate error trends and associated risk factors. Results A total of 74.1% of PRN prescriptions lacked a documented indication, and 91.1% had no recorded dosage interval. Pethidine (32.6%) was the most frequently prescribed PRN medication. The Surgical ICU showed a significantly higher number of errors (p < 0.05). Major predictors of PRN errors included missing dosage intervals and admission to high-dependency wards. Conclusions The high frequency of PRN prescribing errors underscores the urgent need for improved documentation and targeted training. Structured interventions such as electronic prescribing and focused medical education can help reduce errors and improve patient safety. Structured interventions such as electronic prescribing, regulatory enforcement, and focused medical education can help reduce errors and improve patient safety.